2022
DOI: 10.1155/2022/9731800
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Prolyl Endopeptidase Induced by Oxidative Stress in Nucleus Pulposus Cells Aggravates Intervertebral Disc Degeneration

Abstract: A healthy microenvironment of the intervertebral disc tissue is characterized by hypoxia owing to its sparse vascular distribution. Oxidative stress plays a pivotal role in the pathological development of intervertebral disc degeneration (IVDD). We found that the expression of prolyl endopeptidase (PREP) increased in degenerative nucleus pulposus (NP) tissues. The purpose of this study was to determine whether PREP is involved in oxidative-stress-induced IVDD. Tertbutyl hydroperoxide can inhibit the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…115 ROS can inhibit its downstream signal transduction by inhibiting the phosphorylation of PI3K and Akt and promoting PTEN expression. 116,117 In IDD, activation of the PI3K/Akt signalling pathway effectively ameliorated oxidative stress-induced apoptosis, ECM degradation, and cell proliferation of NPCs 118,119 .In addition, Guo et al 120 found that resveratrol (RSV) could promote ECM production and increase the expression of autophagy related markers (beclin-1 and LC-3) to induce cell autophagy to delay IDD. Mechanistic studies revealed that RSV exerted a protective effect through activation of the PI3K/Akt pathway.…”
Section: Pi3k-aktmentioning
confidence: 99%
“…115 ROS can inhibit its downstream signal transduction by inhibiting the phosphorylation of PI3K and Akt and promoting PTEN expression. 116,117 In IDD, activation of the PI3K/Akt signalling pathway effectively ameliorated oxidative stress-induced apoptosis, ECM degradation, and cell proliferation of NPCs 118,119 .In addition, Guo et al 120 found that resveratrol (RSV) could promote ECM production and increase the expression of autophagy related markers (beclin-1 and LC-3) to induce cell autophagy to delay IDD. Mechanistic studies revealed that RSV exerted a protective effect through activation of the PI3K/Akt pathway.…”
Section: Pi3k-aktmentioning
confidence: 99%
“…These studies suggest that p53 induces ECM remodeling by promoting the expression of matrix-degrading enzymes and inhibiting the expression of matrix proteins. In IDD, IL-1β significantly increased the expression level of p53 in NPCs, which resulted in the upregulation of mRNA and protein levels of MMP-3, MMP-13, ADAMTS-4, and ADAMTS-5 and the downregulation of Col II and Agg [ 103 ]. In addition, several studies have shown that abnormal activation of the NF-κB and JNK signaling pathways in IVD is an important factor contributing to IDD progression [ 143 ].…”
Section: The Role Of P53 In Iddmentioning
confidence: 99%
“…Activated NF-κB and JNK signaling pathways upregulate p53 expression, accelerating ECM degradation by promoting the expression of MMPs and ADAMTS and inhibiting the expression of Col II and Agg [ 71 , 217 ]. Recently, Zheng et al [ 103 ] reported that p53 binds to the promoter regions of prolyl endopeptidase to promote their transcription. Overexpression of prolyl endopeptidases impairs the ECM quality of NPCs by inhibiting the expression of Col II and Agg and promoting the expression of MMP3.…”
Section: The Role Of P53 In Iddmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress has been demonstrated to play important roles in the development of IDD [ 13 , 14 ]. Under normal circumstances, the microenvironment of intervertebral disc (IVD) tissue is hypoxic, and there is a dynamic balance between the generation and scavenging of intracellular reactive oxide species [ 15 ]. However, the oxidative stress occurs when this balance is disrupted, which can lead to senescence and apoptosis of nucleus pulposus cells (NPCs), and degradation of extracellular matrix [ 16 ].…”
Section: Introductionmentioning
confidence: 99%